2017
DOI: 10.1021/acs.est.6b02904
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Salinity-Stressed Vibrio sp. and the Effect on the Biofilm Formation on a Nanofiltration Membrane

Abstract: This study evaluated the effects of salinity on the physiological characteristics of Vibrio sp. B2 and biofilm formation on nanofiltration (NF) membrane coupons used in the high recovery seawater desalination process. The test conditions were at 0.6, 1.2, and 2.4 M sodium chloride (NaCl), equivalent to salinity of seawater, brine at 50% and 75% water recovery, respectively. High salinity inhibited the cell growth rate but increased the viability and bacterial membrane integrity. In addition, protein and eDNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 55 publications
(100 reference statements)
0
20
0
Order By: Relevance
“…Parallel research has shown that saline water irrigation can change bacterial metabolic activities and community structures ( Chen et al, 2017 ). Cell growth rate was inhibited by high salinity, but the viability and integrity of the bacterial membrane were increased ( Kim and Chong, 2017 ). The functional structure of a bacterial community was significantly affected by pH ( Joshi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parallel research has shown that saline water irrigation can change bacterial metabolic activities and community structures ( Chen et al, 2017 ). Cell growth rate was inhibited by high salinity, but the viability and integrity of the bacterial membrane were increased ( Kim and Chong, 2017 ). The functional structure of a bacterial community was significantly affected by pH ( Joshi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…To study the extent of biofilm formation, the strains S. aureus and V. cholerae were grown overnight in LB broth media at 37 °C in orbital rotatary shaker that was further diluted to 1:100 into fresh LB sucrose (1% sucrose) 48 and LB saline (2% NaCl) 47 media respectively. V. cholerae is a halophilic microbe and under stress condition, biofilm formation is induced 51 . 100 μl of the diluted culture was put into each well of the 96 well plates containing different concentration of AuNPs-SL and SL (25, 50 and 100 μg/ml) that was incubated for 24 h at 37 °C.…”
Section: Antibiofilm Activity Effect Of Aunps-sl On Inhibition Of Bimentioning
confidence: 99%
“…This difference may result from the diversity of treatment process and the microbial species. Also, when abruptly exposed to the higher salinity environment, bacterial cells might remain in a state of plasmolysis, resulting in the decline of denitrifying activities [64]. Kinyage -N was removed when the salinity was increased from 0 to 3.5%.…”
Section: Reactor Performancementioning
confidence: 99%